Resource utilization and cost effectiveness of treating acute promyelocytic leukaemia using generic arsenic trioxide. (21st December 2019) - Bankar, Aniket; Korula, Anu; Kulkarni, Uday P.; Devasia, Anup J.; NA, Fouzia; Lionel, Sharon; Abraham, Aby; Balasubramanian, Poonkuzhali; Janet, Nancy Beryl; Nair, Sukesh C.; S, Sezlian; Jeyaseelan, Visali; et al.
Summary: Arsenic trioxide (ATO)‐based regimens are the standard of care for treating acute promyelocytic leukaemia (APL) and have replaced chemotherapy‐based approaches. However, the cost of "patented" ATO is prohibitive because of patent rights. "Generic" ATO has been used in a few countries, but its implications for health resource utilization (HRU) and cost of treatment are unknown. We hypothesized that treating APL patients using generic ATO (APL‐ATO) will be cost effective compared to the chemotherapy‐based regimen (APL‐CT). In a single‐centre retrospective study, we used a bottom‐up costing method to compare the direct medical cost of treatment and HRU between APL‐ATO and APL‐CT. These costs and the survival and relapse probabilities were imputed in a three‐state Markov decision model to estimate the cost effectiveness of APL‐ATO compared to APL‐CT. The mean cost of treatment for APL‐ATO ( n  = 30, $8500 ± 2078) was significantly less than for APL‐CT ( n  = 30, $22 600 ± 5528) ( P  < 0·001). APL‐ATO reduced hospitalization, antibiotic and antifungal usage ( P  < 0·001). In the Markov model, five‐year treatment costs were significantly lower for APL‐ATO ($11 131) than for APL‐CT ($17 926) ( P  < 0·001). Treatment cost and health resource utilization were significantly lower for generic ATO‐treated APL patients compared to the chemotherapy‐based regimen.